(untitled) (Journal of Science and Technology Research, 2024)
The injudicious use of antibiotics as growth promoters in poultry rations has caused great concern around the world. Scientists are currently trying to replace broadspectrum antibiotics in animal diets with alternative natural feed additives. The current study aimed to investigate the dietary effect of turmeric rhizome powder (TP) on the growth performance, serum lipid profiles, and intestinal microflora of broiler chickens. A total of 75 Cobb-15 broiler chicks (15-day-old) were randomly distributed into five groups offered with five experimental rations designated as T0 (control diet, without TP), T1 (1 g TP/kg feed), T2 (2.5 g TP/kg feed), T3 (5 g TP/kg feed), and T4 (7.5 g TP/kg feed). Parameters such as body weight gain, total feed intake, and feed conversion ratio (FCR) were used to assess the response of broiler chickens to feed turmeric powder. Supplementation with 5 g TP/kg feed (T3) resulted in the highest increase in body weight with a relatively lower FCR. Serum levels of cholesterol, triacylglycerol, and LDL-cholesterol decreased significantly when supplemented with 5 g TP/kg feed. The bacteriological investigation revealed that a turmeric-supplemented diet significantly lowered the total Salmonella spp. count. The antioxidant property of turmeric rhizome may alleviate stress in broiler chickens. Taken together, these findings indicate that supplementing broiler ration with 5 g TP/kg feed improved growth performance, lipid profiles, and intestinal microflora of broiler chickens, suggesting that turmeric rhizome can be a potential alternative feed additive to synthetic antibiotics for safe and organic poultry meat production. J. of Sci. and Tech. Res. 6(1): 117-124, 2024